(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
Various theoretical researches on foreign direct investment have resulted in a better understanding of the financial mechanism and investor behaviour at both the micro and macro levels, enabling for the emergence of new economic theory. Microeconomic Foreign Direct Investment theories are firm-centered, linked to ownership and internal advantages, and aimed at, market inefficiencies, biases and industrial economics. Furthermore, macroeconomic FDI theories emphasize country-specific characteristics as well as directed international economy and commerce. The Portuguese were the first to establish a textile operation in India in 1500AD, accompanied by British and Dutch East India Companies. Till then FDI has become a key factor for the development of the developing nations and India is one of them. Developed countries enriched with the resources like technology, capital and management skills. They take the comparative advantage by investing in developing countries. Due to the large market size, cheap labour and abundance of natural resources, India has reached under one of the top emerging economies. Various sectors are emerging as a favorite destination for foreign investors. Some of the key fields of FDI are petroleum, mine, coals, and fuel, as well as banks, healthcare, transport, financing, manufacture, and retail. FDI is as much important as a growth engine for India. In 2014 Indian Government has taken important measures such as make in India, reduction in effective corporate tax from 25% to 17%, introduction of production linked incentive scheme in thirteen sectors that works as catalyst for attracting FDI.